Akhlak Tasawuf Dalam Sains Modern - Sholihah, Mar'atus; Jannah, Nur; Afida, Ifa (At-Turost : Journal of Islamic Studies, 2020)
There is a big difference between science and religion, so is between traditional science and modern science. This concept is made by the facts that the development of modern world right now and the industry revolution 4.0 do not have any balance with the morality and religion itself. It is proved by many evidence that most people tend to destroy this planet rather than saving it. Traditional science has a purpose for getting an understanding, but modern science develops science for manipulating nature. The worst thing about this is that, people do not know they have exploited nature this much because this already becomes a culture. Modernity is a culture which extincts traditional culture rather than developing it. This paper offers a new approach of understanding what science is and how humans learn it properly as the world needs. It also shows how important it is to apply moral and religion values in akhlak tasawuf teaching to learn, understand and develop science.